Developing and evaluating a translanguaging-multiliteracies learning design (LDTMP) for student agency in a college English course in China - Zhou, Jie; Lee, Sze Seau; Kew, Si Na (Frontiers in Education, 2025)
Set within the context of a college English course in China, this study introduces an educational approach known as Learning Design based on Translanguaging and Multiliteracies Pedagogy (LDTMP), which aims to foster student agency within higher education. “Translanguaging” refers to the integrated use of multiple languages, and “multiliteracies” pertains to the diverse literacy skills required in today’s multimodal world. The significance of student agency is emphasized as it enables students to take control of their learning process, aligning with the goals of lifelong learning and active citizenship advocated by policies in China. The research employs Design-Based Research (DBR), a method that involves three phases: (1) preliminary research to establish a theoretical foundation, (2) iterative prototype development and classroom implementation, and (3) the formalization of research and design principles. This approach is particularly suitable for integrating innovative pedagogies such as translanguaging and multiliteracies, which are central to the LDTMP framework. The study reports partial findings from the first and second phases of the complete DBR research. In the first phase, literature review contributed to the design and development of a prototype of LDTMP. In the second phase, the prototype of LDTMP was implemented in a college English course and evaluated quantitatively and qualitatively through a pilot study. Results indicated significant differences in LDTMP on student agency compared to other instructional models across dimensions such as self-efficacy beliefs, teacher support, opportunities to influence, and opportunities to make choices.